A descriptive study of treatment provision for problem alcohol drinking in adult males in Khayelitsha, Cape Town, South Africa - Amina Saban; Neo Morojele; Leslie London (BMC, 2017)
Abstract Background Poor, Black African males are underrepresented as patients in facilities that treat problem drinking in Cape Town, South Africa. Reasons for this remain unclear, but factors such as the kinds of treatment provided, perceptions of treatment efficacy, social stigma and traditional treatment beliefs have been suggested as possible barriers to treatment seeking. This descriptive study examined the availability and nature of problem drinking treatment facilities in Khayelitsha, a largely poor township of Black, Xhosa-speaking Africans, on the outskirts of Cape Town. Methods Seven treatment facilities for problem drinking in adult males were identified using data from the Department of Social Development in the City of Cape Town. Staff members were identified as key informants at each of the treatment facilities, and were interviewed using a structured questionnaire. Twelve interviews were conducted. Results Findings indicated that the available alcohol treatment facilities were relatively new, that treatment modalities varied both across and within treatment facilities, and that treatment was provided largely by social workers. Treatment facilities did not accommodate overnight stay for patients, operated during weekday office hours, and commonly referred patients to the same psychiatric hospital. Discussion The study provides a baseline for assessing barriers to treatment for problem drinking in Khayelitsha by highlighting the nature of available facilities as playing a predominantly screening role with associated social work services, and a point of referral for admission to a psychiatric institution for treatment. The social and financial implications of such referral are pertinent to the discussion of treatment barriers. Conclusions Recommendations are made to inform policy towards locally-provided integrated care to improve treatment provision and access.